Participatory Action Research : Theory and Methods for Engaged Inquiry. - Chevalier, Jacques M. (Taylor and Francis, 2013)
This book addresses a key issue in higher learning, university education and scientific research: the widespread difficulty researchers, experts and students from all disciplines face when trying to contribute to change in complex social settings characterized by uncertainty and the unknown. More than ever, researchers need flexible means and grounded theory to combine people-based and evidence-based inquiry into challenging situations that keep evolving and do not lend themselves to straightforward technical explanations and solutions. In this book, the authors propose innovative s.